154k views
5 votes
What’s the answer 4(x+4)=24+6x

2 Answers

1 vote

Answer:

x = -4

Explanation:

[ Step 1: Simplify both sides of the equation ]

4(x + 4 ) = 24 + 6x

(4)(x) + (4)(4) = 24 + 6x (Distribute)

4x + 16 = 24 + 6x

4x + 16 = 6x + 24

[ Step 2: Subtract 6x from both sides ]

4x + 16 − 6x = 6x + 24 − 6x

−2x + 16 = 24

[ Step 3: Subtract 16 from both sides ]

−2x + 16 − 16 = 24 − 16

−2x = 8

[ Step 4: Divide both sides by -2 ]

-2x / -2 = 8 / -2

x = -4

User Ed Manet
by
4.6k points
7 votes

Answer:

x = -4

Explanation:

used app by google called Socratic, it can solve a ton of problems

User Nelson Ramirez
by
4.6k points